New species of the South American loxandrine genus Metoncidus Bates (Coleoptera, Carabidae) - Will,Kipling W. (2004)
Two species are added to the previously monotypic genus Metoncidus Bates, 1871 (Carabidae, Loxandrini): M. epiphytus sp. nov. (type locality Peru: Loreto, Cocha Shinguito) and M. gracilus sp. nov. (type locality Peru: Tambopata, Madre de Dios). Information allowing identification of the genus from among other South American carabid genera and a key to adult individuals of Metoncidus species are provided.